The Impact of organic amendments (vermicompost and fermented cow manure) on managing corn stalk rot disease caused by Fusarium incarnatum - Jamel, Dareen S.; Hatem, Mena Waleed; Kareem, Tariq A. (Universitas Lampung, 2025)
This study investigated the efficacy of organic amendments, specifically vermicompost (V) and fermented cow manure (C), at application rates of 625 and 1250 kg/dunam, in managing corn stalk rot disease caused by Fusarium incarnatum. Maize (Zea mays L.) is a globally vital crop, making the study of its diseases, such as stalk rot, essential for ensuring food security. Field experiments were conducted on five hybrid corn varieties (DKc6664, DKc6777, GS235982, GS235772 and 2341.Rayal) during the spring season of 2024 in Baghdad, Iraq. The results demonstrated that higher application rates (V. 1250 and C. 1250) significantly reduced disease severity and improved plant growth parameters, including plant height, vegetative mass, and yield components. Vermicompost at 1250 kg/dunam (V. 1250) was particularly effective in reducing disease severity in DKc6664 (16.67%) and DKc6777 (16.67%), while fermented cow manure at 1250 kg/dunam (C. 1250) enhanced root development and seed weight in DKc6777. In contrast, F. incarnatum inoculation consistently increased disease severity across all varieties, with the highest severity observed in GS235982 (91.61%). These findings highlight the potential of organic amendments, especially at higher application rates, to improve corn productivity and manage stalk rot disease, even under pathogen pressure.